Matematické Fórum

Nevíte-li si rady s jakýmkoliv matematickým problémem, toto místo je pro vás jako dělané.

Nástěnka
!! 17.06.2018 (Jel.) Khanova škola zve nadšence ke spolupráci na překladech návodů pro učitele a rodiče.
! 04.11.2016 (Jel.) Čtete, prosím, před vložení dotazu, děkuji!
17.01.2016 (Jel.) Rok 2016 s novými a novějšími krystaly od kolegy Pavla!
17.01.2016 (Jel.) Nabídka knih z oborů matematiky, fyziky, chemie
23.10.2013 (Jel.) Zkuste před zadáním dotazu použít některý z online-nástrojů, konzultovat použití můžete v sekci CAS.

Nejste přihlášen(a). Přihlásit

#1 03. 11. 2011 16:41

stuart clark
Příspěvky: 795
Reputace:   
 

Trigonometric equation

solve for $x$

$1+\frac{1}{2\sin (30^0+x)}=\frac{\sin \frac{x}{2}}{\sin (\frac{x}{2}+60^0)}+\frac{\sqrt{3}}{2.\sin (\frac{x}{2}+60^0)}$

Offline

 

#2 16. 03. 2018 16:34 — Editoval laszky (16. 03. 2018 20:03)

laszky
Příspěvky: 801
Škola: MFF UK, FJFI CVUT
Reputace:   50 
 

Re: Trigonometric equation

Firstly we denote $s=\sin\left({\small \frac{x}{2}}\right)$ and $c=\cos\left({\small \frac{x}{2}}\right)$ and adjust all sines as follows

$\sin(30°+x) = \frac{1}{2}\cos x + \frac{\sqrt{3}}{2}\sin x = \frac{1}{2}\,(c^2-s^2) + \sqrt{3}\,cs$

$\sin\left(\frac{x}{2}+60°\right) = \frac{1}{2}\,s + \frac{\sqrt{3}}{2}\,c$.

Next, we remove fractions from the equation and use $c^2=1-s^2$. We obtain the equality

$c(2\sqrt{3}-6s-4\sqrt{3}s^2) = 4s^3-2\sqrt{3}s^2-6s+\sqrt{3}$

Further, we square the whole equation and employ the equality $c^2=1-s^2$ again. This yields

$-16\left(s+\frac{\sqrt{3}}{2}\right)^2\left(s-\frac{\sqrt{3}}{2}\right)\left(4s^3-3s+\frac{\sqrt{3}}{2}\right)=0$

While $s=\frac{\sqrt{3}}{2}$ is the solution of the original equation, $s=-\frac{\sqrt{3}}{2}$ is not.

In order to solve the cubic equation, we use the identity

$4\sin^3 y-3\sin y = \sin^3y + 3\sin y(\sin^2y -1) = \sin^3y - 3\sin y\cos^2 y = $
$ = \sin y(\sin^2y-\cos^2y) -2\sin y\cos^2y=-\sin y\cos(2y)-\sin(2y)\cos y = -\sin(3y)$

Hence $\sin\left(\frac{3}{2}x\right)=\frac{\sqrt{3}}{2}$.

The solutions of the given equation, thus, can be only of the form

$x_1=\frac{2}{3}\pi+4k\pi, \qquad x_2=\frac{4}{3}\pi+4k\pi, \qquad x_3=\frac{2}{9}\pi+\frac{4}{3}k\pi \qquad \mathrm{and}\qquad x_4=\frac{4}{9}\pi+\frac{4}{3}k\pi$.

Plugging them into the original equation, we find out that only $x_1$ and $x_4$ solve it.

Offline

 

Zápatí

Powered by PunBB
© Copyright 2002–2005 Rickard Andersson